An exploration of the role of the therapeutic relationship in the treatment of complex trauma : a psychodynamic-phenomenological case study - Manfroni, Antje (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2008.